Pertinência do projeto universitário latino-americano para a internacionalização da educação superior: um estudo sobre a Unila - Prolo, Ivor (2019)
The Cordoba Movement in Argentina, which took place in 1918, marks the emergence of the typically Latin American university trend, and its main legacy is the commitment to social justice in the quest for a more egalitarian and democratic society. This legacy's internalization can be observed in many public institutions and it strengthens the sense of universities relevance. Since the 21st century, Latin American forums on education have been emphatic in (re) affirming the maxim that higher education is a universal human right, a social necessity and a State's duty. Consistent with the existence of a progressive political leaderships profile in South American countries, a favorable environment is created, in the Educational Mercosul, to foment discussions which consider the legacy and the maxim above-mentioned. Thus, integration via education plays a central role in building an integrative regional and social consciousness based on coexistence and mutual respect, among students and teachers, in internationalized spaces. These spaces happen in actions of internationalization among universities or in institutions created for this purpose. The most intrinsic, authentic and exemplary case of university that internalizes these purposes in Latin America is that of the Federal University of Latin American Integration - UNILA, situated in Foz do Iguaçu, a city located on the tri-border area between Argentina, Brazil and Paraguay. However, despite its coherence with the Latin American conception of university and of imprinting a sense of sociocultural relevance to these ideals, this institution remains in a fragile balance in relation to the university project aligned with the mainstream and the public investment destined to it. In this context, this research is guided by a discussion of the following thesis: the consolidation of a thematic university, committed to Latin American international integration and guided by a sense of socio-cultural relevance, depends on its ability to reconcile both national and the international agenda. The methodological path is associated with the tradition of interpretative research, subordinated to the qualitative approach. The adopted method is the qualitative and unique case study. The essence of the empirical data had as initial point individual and group interviews that happened for three years and were guided by scripts. The research findings were subdivided into three articles (chapters). The main overall results are: i) the imbalance between the founding mission of the researched university and its functioning and institutional expansion; ii) the subordination of the international purpose to the national one (Laws, financing and new governmental interests); iii) the internal difficulty of reaching consensus, without losing focus on the institution's original purposes, in order to institutionalize norms and procedures and to guide leaders' actions in the scope of administrative and academic management. In addition to these, the execution and consolidation of the project of this institution is not an easy undertaking, nor fast and has no foreseeable results. Finally, this research main theoretical contribution is aligned with the lenses of higher education and internationalization with the rescue of the education humanistic view, formulated in the 1990s by UNESCO.